Neural network model for differential GPS - Low, Kwong Hwee. (2008)
The Global Positioning System (GPS) is a worldwide satellite-based system consisting of a constellation of 24 satellites and their ground stations. GPS uses the satellites as reference points to calculate positions accurate to a matter of meters. In fact, with advanced forms of GPS, measurements to better than a centimeter can be made. GPS receivers have been miniaturized to just a few integrated circuits and so are becoming very economical, which makes the technology accessible to virtually everyone. In fact, GPS is finding its way into cars, boats, planes, construction equipment, movie making gear, farm machinery, and even laptop computers.